Influence of Contextual Factors on EFL Mexican Teachers’ Beliefs and the Use of Textbooks - Eliphelet Rivera Cuayahuitl; Celso Pérez Carranza (HOW, 2015)
While much has been written about the use of instructional materials in the field of language education, very few studies have actually studied the impact of the context in the use of materials in teachers’ practices. This work shows the findings of a study about the contextual factors that a group of experienced Mexican teachers believe shaped their lessons. Drawing on qualitative data, the study shows that factors such as the length of courses and lessons, the school facilities, the institutional practices to select textbooks as well as the institutional procedures to supervise teachers’ practices and assessment, explicitly emerged as the most influential in the teachers’ lessons.